Exchange Rate Volatility and Purchasing Power Parity: Does Euro Make Any Difference? - Meher Manzur; Felix Chan (The International Journal of Banking and Finance, 2010)
This paper provides a new test of the purchasing power parity (PPP) and its relevance for the Euro. Principal component analysis (PCA) is employed to construct a pooled measure of inflation for 12 Euro-currency countries. This measure is used to test the PPP for Euro against three major currencies, namely, those of the Japan, UK and USA. The test results are then used to measure the speed of adjustment of the deviations from parity using rolling and recursive regressions procedures. Finally, the forecasting accuracy of the PPP-based Euro exchange rates is compared with those given by the random walk model, and the synthetic Euro series provided by the European Central Bank. In general, the results are supportive of PPP.